2003
DOI: 10.1007/s00027-003-0699-9
|View full text |Cite
|
Sign up to set email alerts
|

The Tagliamento River: A model ecosystem of European importance

Abstract: Abstract. In NE Italy is a remarkable floodplain river that retains the dynamic nature and morphological complexity that must have characterized most Alpine rivers in the pristine stage. This river system, the Fiume Tagliamento, constitutes an invaluable resource not only as a reference site for the Alps, but as a model ecosystem for large European rivers. The Tagliamento has a number of attributes that have not been given due consideration in river ecology: (i) an immense corridor of more than 150 km 2 that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
157
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(161 citation statements)
references
References 50 publications
1
157
0
3
Order By: Relevance
“…For most research and management processes, the dynamics within these existing, modified systems are of great interest. However, understanding natural systems is also important, for example in studying hydromorphic processes and acting as references against which modified dynamics can be compared (Tockner et al, 2003), but to do so requires the effects of widespread modification to be circumvented. Coupled palaeohydrological and palaeoecological studies examining the behaviour of rivers prior to major human modifications provide one possibility (Brown, 2002).…”
Section: Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…For most research and management processes, the dynamics within these existing, modified systems are of great interest. However, understanding natural systems is also important, for example in studying hydromorphic processes and acting as references against which modified dynamics can be compared (Tockner et al, 2003), but to do so requires the effects of widespread modification to be circumvented. Coupled palaeohydrological and palaeoecological studies examining the behaviour of rivers prior to major human modifications provide one possibility (Brown, 2002).…”
Section: Variabilitymentioning
confidence: 99%
“…In Europe, such systems are rare } and therefore valuable (e.g. Fiume Tagliamento; Tockner et al, 2003). Both approaches have weaknesses, stemming from incomplete information in reconstructing the past or questions over the generality of 'model rivers', but nevertheless can provide unique insights into the behaviour of 'natural' rivers.…”
Section: Variabilitymentioning
confidence: 99%
“…Further detailed information on the Tagliamento catchment and the main study area can be found elsewhere (Ward et al 1999;Arscott et al 2002;Tockner et al 2003).…”
Section: Study Sitementioning
confidence: 99%
“…At the same time, it is evident that the degree of deviation from natural conditions for both cases is different. This example can be related to the Italian river Tagliamento which is considered a model ecosystem of an Alpine river with undisturbed, braided channel pattern (Tockner et al 2003). Over the past century, the width and the braiding index of the Tagliamento decreased by half (Surian and Rinaldi 2004), partially as a result of the river adjustment to decreasing bedload supply and partially because of engineering works carried out along the entire reach length.…”
Section: European Standards Of Hydromorphological Assessmentmentioning
confidence: 99%